Characterisation of overloads in fatigue by 2D strain mapping at the surface and in the bulk. Issue 8 (20th May 2016) - Lopez‐Crespo, P.; Mostafavi, M.; Steuwer, A.; Kelleher, J. F.; Buslaps, T.; Withers, P. J.
Abstract: Two complementary experimental techniques have been used to study the evolution of crack‐tip strain fields in a thin (plane stress dominated) compact tension sample following a single overload (OL) event. The total strain has been characterised at the surface by digital image correlation (DIC), while the elastic strain field in the bulk (interior) behaviour has been characterised by means of synchrotron X‐ray diffraction (XRD). Surface and bulk information allowed us to visualise the evolution of the strain fields before the OL event, during the OL event, just after it and at various stages after it. Unlike previous work, complete 2D maps of elastic strains around the crack‐tip were acquired at 60 µm spatial resolution by XRD. The strain data were used to estimate the effective crack driving force at the surface and at the mid plane. The DIC shows less crack opening displacement after overload and the XRD a lower crack‐tip peak stress after OL until the crack has grown past the compressive crack‐tip residual stress after which the behaviour returned to that for the baseline fatigue response. While the compressive residual stress introduced by the OL offsets the crack‐tip stress field as it grows through the overload plastic zone, the changes in crack‐tip stress over each cycle are the same before and at all stages after OL.